2018
DOI: 10.3389/fmicb.2018.01506
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Potential of Lactobacillus paracasei Adjuncts for Flavor Compounds Development and Diversification in Short-Aged Cheddar Cheese

Abstract: The non-starter microbiota of Cheddar cheese mostly comprises mesophilic lactobacilli, such as Lactobacillus casei, Lactobacillus paracasei, Lactobacillus rhamnosus, and Lactobacillus plantarum. These bacteria are recognized for their potential to improve Cheddar cheese flavor when used as adjunct cultures. In this study, three strains of L. paracasei (DPC2071, DPC4206, and DPC4536) were evaluated for their contribution to the enhancement and diversification of flavor in short-aged Cheddar cheese. The strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 45 publications
4
26
1
Order By: Relevance
“…The isolates of Lbc. paracasei are used as the nonstarter lactic acid bacteria in the adjunct culture for semihard and hard cheeses (Peralta et al ; Stefanovic et al ). The analyses of many types of artisan cheeses confirmed that the presence of facultative heterofermenters depends on the ageing of cheese.…”
Section: Discussionmentioning
confidence: 99%
“…The isolates of Lbc. paracasei are used as the nonstarter lactic acid bacteria in the adjunct culture for semihard and hard cheeses (Peralta et al ; Stefanovic et al ). The analyses of many types of artisan cheeses confirmed that the presence of facultative heterofermenters depends on the ageing of cheese.…”
Section: Discussionmentioning
confidence: 99%
“…are another example of bacteria found in raw milk, which has been used for many industrial dairy applications. They can contribute to the quality and nutritional value of dairy products through their proteolytic activity and ability to produce aroma compounds [49]. These genera are one of the dominant bacterial populations isolated from camel milk.…”
Section: Microbiota Of Camel Milkmentioning
confidence: 99%
“… Application in biocatalysis [ 701 ] P. alcaligenes M-1 Alkaline lipases, able to removing fatty stains when used in a washing machine [ 705 ] Pseudomonas plantarii Solvay Enzyme Products, Applicable for is a nonionic and/or anionic detergent formulation [ 706 ] Chromobacterium viscosum Detergent formulations containing alkaline lipase used in laundry detergent “Top” [ 707 ] Acinetobacter sp. Degrading 60–65% of the fatty material in the waste water management [ 708 ] Bacillus thermocatenulatus Used in medical industry [ 641 ] Lactobacillus casei, Lactobacillus paracasei, Lactobacillus rhamnosus, and Lactobacillus plantarum. Cheese Industry for improvement of flavor [ 709 ] Penicillium roquefortii Cheese Industry for cheese ripening [ 710 ] Staphylococcus warneri, S. xylosus Production of flavour esters [ 711 ] Pseudomonas cepacia Biodiesel fuel production [ 712 ] Pseudomonas sp.…”
Section: Sources For Microbial Lipasesmentioning
confidence: 99%
“…Other benefits of microorganisms are high productivity of substrate conversion into product, environmental conditions versatility, and simplicity of genetic operation and in harvesting situations [ 640 ]. Lipases have capabilities to catalyze the same reaction using from different sources, but the microbial lipases are mostly used for biodiesel production like Aspergillus niger , Candida antarctica, Candida rugosa , Chromobacterium viscosum , Mucor miehei , Lactobacillus plantarum, Pseudomonas cepacia , Pseudomonas fluorescens , Photobacterium lipolyticum , Rhizopus oryzae , Streptomyces sp., and Thermomyces lanuginose, Burkholderia cepacia, Bacillus subtilis Q1 KX712301 [ 293 , 641 ]. Candida rugosa yeast is mostly used for lipase production.…”
Section: Industrial Applications Of Lipasesmentioning
confidence: 99%